2003
DOI: 10.1002/macp.200350013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐Induced Crystal/Conformation Transformations in Syndiotactic Polystyrene Films Treated with Different Solvents

Abstract: Solution‐crystallized or solvent‐induced crystal forms and transitions of these crystals upon post‐annealing in solvent‐treated syndiotactic polystyrene (sPS) (films cast from o‐dichlorobenzene or immersed in 1,2‐dichloroethane, respectively) were investigated via wide‐angle X‐ray diffraction (WAXD), differential scanning calorimetry (DSC), and Fourier‐transform infrared (FTIR) spectroscopy. IR spectra in the frequency range of 720–820 cm−1, which is attributed to the CH out‐of‐plane bending of the phenyl rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…sPS is a polymorphic material possessing various crystal modifications, typically the α-form with hexagonal, the β-form with orthorhombic, and both γ- and δ-forms with monoclinic lattices. ,, Both α- and β-forms are mainly derived from melt crystallization, whereas the γ- and δ-forms are obtained from solvent-induced crystallization. It has been demonstrated that the absorbance peak at 1222 cm −1 is associated with the crystalline phase, with TTTT chain conformation existing in the α- and β-form sPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sPS is a polymorphic material possessing various crystal modifications, typically the α-form with hexagonal, the β-form with orthorhombic, and both γ- and δ-forms with monoclinic lattices. ,, Both α- and β-forms are mainly derived from melt crystallization, whereas the γ- and δ-forms are obtained from solvent-induced crystallization. It has been demonstrated that the absorbance peak at 1222 cm −1 is associated with the crystalline phase, with TTTT chain conformation existing in the α- and β-form sPS.…”
Section: Resultsmentioning
confidence: 99%
“…Also included is the WAXD pattern of the as-spun fiber mats, which merely shows the amorphous halo. After vapor treatment, the diffraction peaks at 2θ = 8.4° and 2θ = 10.0° are the fingerprints of the δ-form sPS, ,, which correspond to the (010) and (2̅10) reflections, respectively. Additional broad diffraction peaks at 2θ = 15.8°, 19.5°, and 23.5° are also discernible.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically this effect was explained by a model composed of the localized electrons and lattices. The polymorphology and crystal transition of polythiophene and polystylene on the solvent vapor and thermal treatment were also reported [14,15].…”
Section: Resultsmentioning
confidence: 93%
“…Possible factors were further surveyed. A literature survey indicates that gelation/micellization, phase separation, and melting/reorganization have been reported to interpret exotherms and endotherms in DSC. Except for reorganization, gelation and phase separation can produce turbid or bluish solutions. Turbid solutions are due to light scattering because of the formation of micro- and macroscale structures in solution.…”
Section: Resultsmentioning
confidence: 99%